Specialized neurological neurosurgical intensive care medicine - Kuramatsu, J. B.; Huttner, Hagen; Schwab, Sibylle (Der Nervenarzt, 2016)
In Germany dedicated neurological-neurosurgical critical care (NCC) is the fastest growing specialty and one of the five big disciplines integrated within the German critical care society (Deutsche Interdisziplinäre Vereinigung für Intensiv- und Notfallmedizin; DIVI). High-quality investigations based on resilient evidence have underlined the need for technical advances, timely optimization of therapeutic procedures, and multidisciplinary team-work to treat those critically ill patients. This evolution has repeatedly raised questions, whether NCC-units should be run independently or better be incorporated within multidisciplinary critical care units, whether treatment variations exist that impact clinical outcome, and whether nowadays NCC-units can operate cost-efficiently? Stroke is the most frequent disease entity treated on NCC-units, one of the most common causes of death in Germany leading to a great socio-economic burden due to long-term disabled patients. The main aim of NCC employs surveillance of structural and functional integrity of the central nervous system as well as the avoidance of secondary brain damage. However, clinical evaluation of these severely injured commonly sedated and mechanically ventilated patients is challenging and highlights the importance of neuromonitoring to detect secondary damaging mechanisms. This multimodal strategy not only requires medical expertise but also enforces the need for specialized teams consisting of qualified nurses, technical assistants and medical therapists. The present article reviews most recent data and tries to answer the aforementioned questions.
EVALuna2:22466